(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Background and introduction: Burn injuries constitute a significant public health concern. WHO has stated in one of its articles that every year approximately 265,000 lives are lost globally due to fires with a staggering 96% of these fire-related burn fatalities occurring in low and middle-income countries. Materials and methods: Considering that an autopsy based retrospective study was done in the Department of Forensic Medicine and Toxicology, N. R. S Medical College and Hospital, Kolkata. The study was done over three years from January 2020 to December 2022. All burn cases brought for autopsy during this study period were included in the present study. Results: The main focus of this study was on the socio demographic pattern, gender, age, and severity of burns which signified that incidence was higher in the urban population as compared to the rural. Moreover, married females in the age group of 21 to 50 years were more commonly involved. Most of the study subjects survived for 24-72 hours from the time of incidence. Conclusion: Urban population and females with young to late adult group are more prone to burn incidence.